1922
DOI: 10.1111/j.1096-3642.1922.tb01841.x
|View full text |Cite
|
Sign up to set email alerts
|

The Vertebrate Fauna of Houtman's Abrolhos (Abrolhos Islands), Western Australia.

Abstract: SUMMARY. Mammals.—The two indigenous species of Mammals are only found in the Wallaby Group, the Wallaby on both the large islands, the Rat, as far as is known, only on East Wallaby Island. The latter is probably, and the former certainly, subspecificailly distinct from the mainland species. Snakes.—The three species of snakes do not appear to differ from the mainland forms. At present two have been found only on West Wallaby Island and the third on East Wallaby Island. Lizards.—‐Four families are represented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1956
1956
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The gidgee skink (Egernia stokesii) is commonly described as gregarious (Alexander 1922;Swan 1990), and can distinguish chemical stimuli from group or non-group conspecifics . Genetic studies (Gardner 1999;Gardner et al 2000Gardner et al , 2001 have suggested a family structure within social groups.…”
Section: Introductionmentioning
confidence: 99%
“…The gidgee skink (Egernia stokesii) is commonly described as gregarious (Alexander 1922;Swan 1990), and can distinguish chemical stimuli from group or non-group conspecifics . Genetic studies (Gardner 1999;Gardner et al 2000Gardner et al , 2001 have suggested a family structure within social groups.…”
Section: Introductionmentioning
confidence: 99%
“…Even surveys of historically well collected areas for reptiles, such as on the central west coast of Western Australia (Alexander 1922;Storr et al 1983;Maryan 2005), can lead to exciting discoveries of new species. Their detection on the Abrolhos Islands represented a major addition to the herpetofauna of this remote archipelago, an area that had been regularly visited and collected for nearly 100 years.…”
Section: Discussionmentioning
confidence: 99%
“…The herpetofauna of the Geraldton region (including the Houtman Abrolhos) is exceptionally diverse and has a long history of surveys (Alexander 1922;Storr et al 1983;Maryan 2005). More recently, additional surveys to document the herpetofauna have resulted in no new species being recorded for the Houtman Abrolhos, but several new records of species being found on individual islands (How et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…NI is a more recently formed sand island and the resident tammar wallaby population must have either naturally dispersed from EWI and/or WWI, or been introduced. The first recorded observation of a tammar wallaby on NI was in 1928 following their introduction (source population unknown) as a potential food source for stranded fisherman (Alexander 1922;Storr 1960;Poole et al 1991). This introduction was thought to be unsuccessful and the population was subsequently reported extinct (Storr 1960).…”
Section: Introductionmentioning
confidence: 97%
“…West Wallabi Island (WWI) is the largest of the three (587 ha) and became separated from the adjacent East Wallabi Island (EWI: 307 ha) 6,000 years ago (Peltier 2004). EWI and WWI are continental islands and tammar wallabies became isolated from the mainland following rising sea levels 11,500 years ago at the end of the last glacial maximum (Alexander 1922;Storr 1965). They are geographically close (1.9 km apart) (GeoscienceAustralia 2005) and since much of this distance is exposed at low tide (BOM 2008) it is believed that wallabies can travel between them (Cooper and McKenzie 1997).…”
Section: Introductionmentioning
confidence: 99%